THE EFFECT OF TAXPAYER AWARENESS, TAX OFFICER SERVICES AND TAX SANCTIONS ON TAXPAYER COMPLIANCE IN TAXPAYER SERVICE OFFICES PRATAMA JEMBER - Fendi Chandra Setiawan; Karim Budiono; Wiwik Fitria Ningsih (LPPM Institut Teknologi dan Sains Mandala, 2021)
This study aims to determine the effect of taxpayer awareness, tax officer services and tax sanctions on tax compliance of free workers in the Jember Pratama tax service office. The data used in this study are primary data collected by survey method using questionnaire media. The data processing method uses multiple regression analysis methods with the help of the SPSS 18 analysis program. The results of hypothesis testing show that taxpayer awareness, tax officer services and tax sanctions have a positive and significant effect on individual taxpayer compliance with independent workers. Keywords: Taxpayers, Taxpayer Compliance, Taxpayer Awareness, Tax Officer Services, Tax Sanctions, Self-employment, Individual Taxpayers